Trends in Neonatal Mortality as an Indicator of Basic Emergency Obstetric and Neonatal Services (PONED) Readiness in Tabanan, 2019–2023 - Imelda Rismayani Gampur (CV. Get Press Indonesia, 2025)
Neonatal mortality is a sensitive indicator of health system readiness in handling emergency obstetric and neonatal cases. Although Tabanan Regency reports high coverage of skilled birth attendance (>95%) and postnatal visits (KN1 and KN3 >99%), preventable neonatal deaths persist annually.This study aimed to analyze neonatal mortality trends in Tabanan Regency from 2019 to 2023 and examine their association with the readiness of Basic Emergency Obstetric and Neonatal Services (PONED). A descriptive quantitative approach using secondary data from district and provincial health profiles (2019–2023) was applied. Key indicators included neonatal mortality rate (NMR), causes of death, and service readiness components. Data were analyzed through trend visualization and determinant mapping.The NMR peaked at 9.0 per 1,000 live births in 2022 and declined to 7.2 in 2023. Leading causes included prematurity/low birth weight (28.2%), asphyxia (18.4%), and infection (14.6%). Despite service coverage being consistently high, findings indicate persistent gaps in readiness particularly in emergency referrals, skilled provider availability, and resuscitation facilities. Neonatal mortality trends in Tabanan reflect underlying limitations in emergency obstetric preparedness. Strengthening PONED readiness through clinical skill development, equipment availability, and efficient referrals is crucial to reducing neonatal deaths. NMR should be considered a proxy indicator of obstetric emergency readiness in decentralized health systems.